DIAGNOSIS AND TREATMENT SPONDYLODISCITIS : THE LITERATURE REVIEW - Susilo, Dhanang (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
In many regions of the globe, pyogenic spondylitis remains a significant concern. It is a disorder that affects a very small proportion of the population, but it can be quite severe and even fatal. Frequently, it is difficult to make a diagnosis due to the absence of evident signs or symptoms. It encompasses a vast array of clinical entities, including pyogenic spondylodiscitis, discitis, vertebral osteomyelitis, and spinal osteomyelitis, among others. The success rates of conservative treatment are comparable to those of surgical treatment, but complications and mortality rates are lower. In the absence of a clear indication for surgical intervention, conservative treatment should be considered first. Patients with cervical tract or tuberculous spondylodiscitis should endure closer diagnostic and clinical monitoring due to the increased risk of developing bone collapse and neurological deficits.